ARENA PRODUKSI KULTURAL DAN KEKERASAN SIMBOLIK - Syahril, Syahril (SCAD Independent, 2014)
This thesis deals with two things, the arena of cultural production and symbolic violence in a novel titled Banât al-Riyâdh (BR). The novel is chosen because it exposes various women’s problems in Saudi Arabia such as their struggle and demand for modernity which are considered as against tradition, strict social convention and sexual ethics in the kingdom. The novel, which represents a cultural battle, deserves to be examined since it exerts a tremendous effect on symbolic violence. The writer analyzes it by applying Pierre Bourdieu’s perspective. The research is aimed at looking at the tension between modernity and tradition which eventually led to the creation of the novel. It is based on two concepts proposed by Pierre Bourdieu, Habitués and arena, which are bolstered by concepts of symbolic power, strategy, and struggle for achieving the symbolic and material power through economic, cultural, and symbolic capitals. For Bourdieu, all human acts occur in the social sphere that suggests an arena of resources struggle. Individuals, institutions, and other agents attempt to distinguish themselves from the other with the intention of obtaining useful and valuable capitals in the arena. Concerning symbolic power, the writer thinks that the novel shows the symbolic violence in numerous forms, like state, patriarchy, and family violence.